Programa manejo de las emociones “Colores del atardecer” en comunidad diagnosticada con accidente cerebrovascular de la ciudad de Ibagué (2023)
The purpose of this work is to create and implement an emotion management program in the community diagnosed with stroke in the city of Ibagué, to determine its effectiveness by finding statistically significant results through the pre-test post-test evaluation of the MSCEIT questionnaire. Mayer and Salovey, since currently and in the course of history according to various investigations it is a topic that has not received attention, because there is no psychological/emotional treatment implemented in public hospitals, or non-profit entities in a manner free, since in addition very few private entities care for it and if so, access is limited since it is economically inaccessible, and this generates negative moods and affects reintegration into social life after the injury